Stress and blood pressure changes among male army population in Kuching, Sarawak - Siti Fatimah, bt Sa'at (Faculty of Medicine & Health Sciences, 2008)
Studies shown that stress was categorized as ones of mentally appraisal, and it is related to changes on the blood pressure. A total of 72 army personnel were assigned by the management at Markas 3 Devisyen, Kuching to participate in this research to determine the relationship between stress and blood pressure.